Impaired cAMP processivity by phosphodiesterase-protein kinase A complexes in acrodysostosis - Venkatakrishnan, Varun; Ghode, Abhijeet; Tulsian, Nikhil K.; Anand, Ganesh S. (Frontiers in Molecular Biosciences, 2023)
Acrodysostosis represents a group of rare genetic disorders characterized by defective skeletal development and is often accompanied by intellectual disabilities. Mutations in the 3’5’cyclic 5’AMP (cAMP)-dependent Protein Kinase (PKA) type I regulatory subunit isoform α (RIα) and phosphodiesterase (PDE) PDE4D have both been implicated in impaired PKA regulation in Acrodysostosis. How mutations on PDEs and RIα interfere with regulation of cAMP-PKA signaling is not understood. cAMP-PKA signaling can be described in two phases. In the activation phase, cAMP binding to RIα dissociates the free C-subunit. PDEs hydrolyze cAMP bound to RIα, priming the cAMP-free RIα for reassociation with the C-subunit, thereby completing one PKA activation cycle. Signal termination is thus critical for resetting PKA to its basal state and promoting adaptation to hormonal hyperstimulation. This proceeds through formation of a transient signal termination RIα:PDE complex that facilitates cAMP channeling from the cAMP-binding domain of RIα to the catalytic site of PDE. Signal termination of cAMP-PKA proceeds in three steps: Step 1) Channeling: Translocation of cAMP from the CNB of RIα to the PDE catalytic site for hydrolysis Step 2) Processivity: Binding of free cAMP from the cytosol at both CNBs of RIα and Step 3) Product (5’AMP) release from the PDE hydrolysis site through competitive displacement by a new molecule of cAMP that trigger subsequent activation cycles of PKA. We have identified the molecular basis for two acrodysostosis mutants, (PDE8 T690P) and RIα (T207A) that both allosterically impair cAMP-PKA signal termination. A combination of amide hydrogen/deuterium exchange mass spectrometry (HDXMS) and Fluorescence Polarization (FP) reveal that PDE8 T690P and RIα T207A both blocked processive hydrolysis of cAMP by interfering with competitive displacement of product 5’AMP release from the nucleotide channel at the end of each round of cAMP hydrolysis. While T690P blocked product 5’AMP release from the PDE, T207A greatly slowed release of substrate from RIα. These results highlight the role of processivity in cAMP hydrolysis by RIα:PDE termination complexes for adaptation to cAMP from GPCR hyperstimulation. Impairment of the signal termination process provides an alternate molecular basis for acrodysostosis.